2020
DOI: 10.1177/0956462420960602
|View full text |Cite
|
Sign up to set email alerts
|

HIV-related enacted stigma and increase frequency of depressive symptoms among Thai and Cambodian adolescents and young adults with perinatal HIV

Abstract: HIV-related enacted stigma and social problems may increase risk for depression and/or behavioral problems among adolescents and young adults with perinatal HIV(AYA-PHIV), yet few studies have explored stigma in AYA-PHIV residing in low-to-middle income regions, including Southeast Asia. We assessed HIV-related enacted stigma and social problems in AYA-PHIV who participated in the RESILIENCE study (clinicaltrials.gov identification: U19AI53741) in Thailand and Cambodia using specific questions during structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…4) The Patient Health Questionnaire for Adolescents (PHQ-A, validated Thai version) was used to assess depressive symptoms in the past 2 weeks, with questions on suicidality in the past month and over a lifetime. Depressive symptoms were classified by score as mild (5-9), moderate (10)(11)(12)(13)(14), moderately severe (15)(16)(17)(18)(19) and severe (20)(21)(22)(23)(24)(25)(26)(27). A PHQ-A score ≥10 was considered to represent significant depression [22,23].…”
Section: Data Collection and Toolsmentioning
confidence: 99%
See 2 more Smart Citations
“…4) The Patient Health Questionnaire for Adolescents (PHQ-A, validated Thai version) was used to assess depressive symptoms in the past 2 weeks, with questions on suicidality in the past month and over a lifetime. Depressive symptoms were classified by score as mild (5-9), moderate (10)(11)(12)(13)(14), moderately severe (15)(16)(17)(18)(19) and severe (20)(21)(22)(23)(24)(25)(26)(27). A PHQ-A score ≥10 was considered to represent significant depression [22,23].…”
Section: Data Collection and Toolsmentioning
confidence: 99%
“…A PHQ-A score ≥10 was considered to represent significant depression [22,23]. 5) The Generalized Anxiety Disorder 7-item test (GAD-7, validated Thai version) was used to assess anxiety symptoms, classified by scores as minimal (1-4), mild (5-9), moderate (10)(11)(12)(13)(14) and severe (15)(16)(17)(18)(19)(20)(21). Scores ≥10 were considered significant [24].…”
Section: Data Collection and Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…These development changes, coupled with the various types of HIV-related stigma experienced by AYA (including structural, internalized, perceived, experienced, and anticipated stigma), make HIV-related stigma among AYA a multidimensional determinant of health outcomes; appropriate measurement tools are needed to accurately assess the potentially critical causal factor. [38][39][40][41] A systematic review of quantitative measures used to assess stigma among pediatric populations (ie, the Perceived Public Stigma Against Children Affected by HIV, Brief HIV Stigma by Association Scale), and especially the global prominence of variations (ie, shorter versions or the full version) of the HIV Stigma Scale, 42 found that few of the existing HIV-related stigma scales were validated for use among individuals aged 18 years or younger, with only some using psychometric techniques to validate measures with target populations. 42 Despite its high use among pediatric populations, the original HIV Stigma Scale, which includes 40 items across 4 subscales-personalized stigma, disclosure, self-image, and public attitudes-was originally validated among adults living with HIV in the United States; few studies both adapt and validate this scale for use among younger populations.…”
Section: Introductionmentioning
confidence: 99%
“…These development changes, coupled with the various types of HIV-related stigma experienced by AYA (including structural, internalized, perceived, experienced, and anticipated stigma), make HIV-related stigma among AYA a multidimensional determinant of health outcomes; appropriate measurement tools are needed to accurately assess the potentially critical causal factor. 38–41…”
Section: Introductionmentioning
confidence: 99%